Cytokinin response induces immunity and fungal pathogen resistance, and modulates trafficking of the PRR LeEIX2 in tomato. (25th August 2020) - Gupta, Rupali; Pizarro, Lorena; Leibman‐Markus, Meirav; Marash, Iftah; Bar, Maya
Abstract: Plant immunity is often defined by the immunity hormones: salicylic acid (SA), jasmonic acid (JA), and ethylene (ET). These hormones are well known for differentially regulating defence responses against pathogens. In recent years, the involvement of other plant growth hormones such as auxin, gibberellic acid, abscisic acid, and cytokinins (CKs) in biotic stresses has been recognized. Previous reports have indicated that endogenous and exogenous CK treatment can result in pathogen resistance. We show here that CK induces systemic immunity in tomato ( Solanum lycopersicum ), modulating cellular trafficking of the pattern recognition receptor (PRR) LeEIX2, which mediates immune responses to Xyn11 family xylanases, and promoting resistance to Botrytis cinerea and Oidium neolycopersici in an SA‐ and ET‐dependent mechanism. CK perception within the host underlies its protective effect. Our results support the notion that CK promotes pathogen resistance by inducing immunity in the host. Abstract : Host CK perception induces systemic immunity in tomato, modulating cellular trafficking of the pattern recognition receptor (PRR) LeEIX2 and promoting resistance to fungal pathogens in an SA‐ and ET‐dependent mechanism.